Education 3640. Problems and issues in special education. No. 09. Counselling needs in the high school. - Nesbit, W. C. (Wayne C.), 1943- (Teacher); Karagianis, Leslie D. (Teacher); Memorial University of Newfoundland. Division of Educational Technology (Producer)
Dr. Nesbit and Dr. Karagianis interview Brenda Smith, special education teacher, on the changing role of the school counsellor, particularly with the movement toward integration. "L. Karagianis, W. Nesbit and Brenda Smith"